Is this ln(x^3) or (ln x)^3?
If it's the first, the answer is y' = 3/x.
If it's the second, the answer is y' = 3 (ln x)^2 / x.
Cheers.
2006-12-17 16:36:20
·
answer #1
·
answered by Mattvayne 3
·
0⤊
0⤋
There are two ways you can approach this. You can either use the log rule and then take the derivative, or take the derivative now. I'll show you both methods.
Right now, I'll solve it as is.
y = ln(x^3). Then, since the derivative of ln(x) is 1/x, but the inside is NOT x, by the chain rule, we have to multiply by the derivative of the inside (x^3).
y' = [1/(x^3)] [3x^2]
y' = [3x^2]/[x^3] = 3/x
Method 2: Recognize that y = ln(x^3) is the same as y = 3ln(x); that is, by the log rule that
log[base b](a^c) = c * log[base b](a)
So let's differentiate.
y = 3ln(x)
y' = 3(1/x) = 3/x, which is the EXACT same answer as above; the only difference is, no chain rule was involved.
2006-12-17 16:43:36
·
answer #2
·
answered by Puggy 7
·
0⤊
1⤋
Wow, how sweet and particular. You do recognize that to be bipolar, he has 2 diverse personalities. Do both halves of him opt for you both? If no longer, perchance you may reduce him in 1/2, and promises the undesirable 1/2 to his Fluffin. close to his puppy named Fluffin, is Stooge attempting to assert he's a "Stud Muffin with Fluffin"? both that, or supply Fluffin away to the interior sight zoo. I hear they could use more beneficial foodstuff for the lions and tigers. i presumed Stooge also had a puppy gerbil too? ask your self what he does with that little creature?
2016-11-27 01:26:56
·
answer #3
·
answered by ? 4
·
0⤊
0⤋
the derivative of lnx =1/x
1/x^3 (x^3)' =
1/x^3 (3x^2)=
3x^2/x^3=
3/x
2006-12-17 16:35:17
·
answer #4
·
answered by Anonymous
·
0⤊
1⤋
Well, it depends on if you mean ln(x^3) or (ln(x))^3.
For ln(x^3), dy/dx = 3/x
For (ln(x))^3, dy/dx = (3 ln(x)^2)/x
Okay, first one is pretty simple, pull out the 3 with a log rule and then just derive.
The second one is a composite deriv.
2006-12-17 16:39:38
·
answer #5
·
answered by Mike J 3
·
0⤊
1⤋
use the chain rule
3x^2 /(x^3) = 3/x
2006-12-17 16:35:49
·
answer #6
·
answered by polloloco.rb67 4
·
0⤊
1⤋
1/x^3 *3x^2
=3/x
2006-12-17 16:35:31
·
answer #7
·
answered by raj 7
·
0⤊
1⤋
y'=(1/x^3)*3x^2 //chain rule, power rule
y'=3x^2/x^3 //Simplify
y'=3/x
2006-12-17 16:36:37
·
answer #8
·
answered by Keith 1
·
0⤊
1⤋
y= ln(x^3)
y' = (3x^2)/x^3
y' = 3/x
2006-12-17 16:53:34
·
answer #9
·
answered by Helmut 7
·
0⤊
1⤋